2018
DOI: 10.1002/jcu.22657
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and reliability of bedside thoracic ultrasound in detecting pulmonary pathology in a heterogeneous pediatric intensive care unit population

Abstract: Purpose: This study was designed to access sensitivity and specificity of detection of lung abnormalities by the ultrasound (US) done by PICU providers of varying levels of experience compared to CXR and to assess the inter-rater reliability in the interpretation of the USG findings.Methods: Up to three US examinations were performed on patients meeting eligibility criteria. US examinations were reported by the operator and remotely by an expert reader. Both operator and readers interpretation were correlated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…We thank Sabour et al for their interest in our paper 1 and welcome their suggestions. They pointed out that Cohen's kappa coefficient is influenced by the prevalence of each category.…”
Section: Dear Editormentioning
confidence: 90%
“…We thank Sabour et al for their interest in our paper 1 and welcome their suggestions. They pointed out that Cohen's kappa coefficient is influenced by the prevalence of each category.…”
Section: Dear Editormentioning
confidence: 90%
“…The agreement between study physicians and expert readers increased gradually, peaking at six months of independent scanning after a five month period of supervised training [100]. In another prospective observational study, novel operators performing LUS showed greater sensitivity and less specificity detecting pneumonia compared to expert ones [38]. Agreement was very good among experts, in particular for the identification of consolidation patterns.…”
Section: Strengths and Limits Of Lus In Childrenmentioning
confidence: 93%
“…In the last years, LUS has been studied to test its efficacy in diagnosing pneumonia in children, with generally good results. When compared with chest X-ray and clinical scores, LUS showed good sensitivity and specificity [6,10,[31][32][33][34][35][36][37][38][39]. Moreover, LUS seemed to have greater sensitivity and less specificity than CXR, suggesting its usefulness as a screening tool for pneumonia [6,10,40].…”
Section: Lus In Pneumoniamentioning
confidence: 99%
“…The authors reported that overall agreement between the operator and reader of the US was 0.53. Also, the agreement was highest with an expert‐expert pair (0.75) and lowest with a novice‐expert pair (0.27) …”
Section: The Kappa and Weighted Kappa Values For Calculating Agreemenmentioning
confidence: 99%
“…We read with great interest the article recently published by Tripathi and colleagues in a recent issue of the Journal of Clinical Ultrasound . The second purpose of the authors was to investigate the interrater reliability in the interpretation of thoracic sonograms performed by pediatric intensive care unit (PICU) providers with varying levels of expertise . The interrater agreement between operators and the readers was assessed with Cohen's kappa coefficient on 135 ultrasound (US) examinations performed on 91 patients.…”
Section: The Kappa and Weighted Kappa Values For Calculating Agreemenmentioning
confidence: 99%